2019
DOI: 10.1111/jgs.15846
|View full text |Cite
|
Sign up to set email alerts
|

The Future of the Home Care Workforce: Training and Supporting Aides as Members of Home‐Based Care Teams

Abstract: Home health, home care, and personal care aides provide most of the paid hands-on care delivered to seriously ill, functionally impaired individuals in their homes, assisted living, and other noninstitutional settings. This workforce delivers personal care, assistance with activities of daily living, and emotional support to their patients. They are often the eyes and ears of the health system, observing subtle changes in condition that can provide important information for clinical decision making and therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…(Home Care Worker) Second, there is a systematic lack of awareness of their role by other providers. Third, working conditions can be poor and isolating [16,17]. Despite this, studies have shown that HCWs generally like their jobs, find them meaningful, and can have a positive impact on patient outcomes, when utilized at their skill level [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…(Home Care Worker) Second, there is a systematic lack of awareness of their role by other providers. Third, working conditions can be poor and isolating [16,17]. Despite this, studies have shown that HCWs generally like their jobs, find them meaningful, and can have a positive impact on patient outcomes, when utilized at their skill level [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the pandemic, for example, direct care workers played an essential role in reducing the burden on hospitals by caring for COVID-19–positive individuals in place or post-discharge. In general, as the often-quoted “eyes and ears” of the interdisciplinary care team ( Stone & Bryant, 2019 ), direct care workers also help reduce avoidable hospitalizations—a common performance measure—and other adverse health outcomes by observing, recording, and reporting changes of condition that may require clinical attention (and in many cases, by directly performing or assisting with tasks that are necessary to manage individuals’ health outside the hospital). With policymakers, payers, and health systems increasingly focused on improving service quality while reducing costs, it is becoming both feasible and necessary to quantify direct care workers’ impact on hospitalization rates and other outcomes, and thereby to generate the political will to improve their jobs and elevate their role.…”
Section: Aligning the Moral And Materials Value Of Direct Carementioning
confidence: 99%
“…Similar conclusions were offered by a report of the Institute of Medicine [25] that called states to establish basic training requirements and competencies to ensure the development of a high-quality home care workforce. In this context, scholars describe the limited attention and investment in competency-based training for this workforce [26]. The current study offers an observation of the development and implementation of such a program and an analysis of the program's efforts to create a new profession in the field of long-term care for older adults, namely community care.…”
Section: Discussionmentioning
confidence: 99%